The Use of TikTok Videos to Increase Seventh Grade Students’ Vocabulary Mastery - Sheila Sarlina Shanda; Abd. Kamaruddin; Maf'ulah Maf'ulah; Aminah Suriaman (Hasanuddin University, 2026)
This study aimed to determine whether TikTok videos can increase seventh-grade students’ vocabulary mastery at MTsN 2 Kota Palu. A quantitative approach with a quasi-experimental design was adopted to compare two existing classes. Class VII E functioned as the experimental class, while Class VII F served as the control class. The total population consisted of 272 seventh-grade students. Although each selected class had 34 students, only 20 students from each class were included in the analysis because they completed all stages of the study. In the experimental class, TikTok videos served as the main medium for presenting vocabulary materials, whereas the control class followed conventional instruction. Vocabulary achievement was measured through tests consisting of multiple-choice, matching, and completion items, which were given before and after the learning process. The result showed that the experimental class achieved a higher score increase, from 15.47 in the pre-test to 83.29 in the post-test. Meanwhile, the control class increased from 14.64 to 73.29. The paired-samples t-test generated a p-value lower than 0.05 (p < 0.001), indicating that Ha was accepted and Ho was rejected. Therefore, TikTok videos can be considered effective in increasing the vocabulary mastery of seventh-grade students at MTsN 2 Kota Palu.